2000
DOI: 10.1021/bi001815n
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of the 26S Proteasome Is Regulated by Phosphorylation of the p45/Rpt6 ATPase Subunit

Abstract: We investigated whether the assembly/disassembly of the 26S proteasome is regulated by phosphorylation/dephosphorylation. The regulatory complex disassembled from the 26S proteasome was capable of phosphorylating the p45/Sug1/Rpt6 subunit, suggesting that the protein kinase is activated upon dissociation of the 26S proteasome or that the phosphorylation site of p45 becomes susceptible to the protein kinase. In addition, the p45-phosphorylated regulatory complex was found to be incorporated into the 26S proteas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
95
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(100 citation statements)
references
References 28 publications
2
95
2
Order By: Relevance
“…For example, phosphorylation of the 20 S proteasome ␣ subunit C8 substantially affects the stability of the 26 S proteasome (29). In addition, phosphorylation of Rpt6 promotes the association of the regulatory complex with the 20 S proteasome to form the 26 S proteasome (32). In contrast, the present study shows that ASK1 does not affect the assembly of the native 26 S proteasome.…”
Section: Discussioncontrasting
confidence: 52%
“…For example, phosphorylation of the 20 S proteasome ␣ subunit C8 substantially affects the stability of the 26 S proteasome (29). In addition, phosphorylation of Rpt6 promotes the association of the regulatory complex with the 20 S proteasome to form the 26 S proteasome (32). In contrast, the present study shows that ASK1 does not affect the assembly of the native 26 S proteasome.…”
Section: Discussioncontrasting
confidence: 52%
“…36), and the phosphorylation of C8 by casein kinase 2 was suggested to increase the stability of the 26S proteasome (37). Satoh et al (38) suggested that dephosphorylation of proteasome structures elicits the dissociation of the 26S proteasome to the 20S proteasome and the regulatory complex. In addition, phosphorylation of several ATPase subunits of 26S in human lung cancer cell lines was found by two-dimensional gel analysis (39).…”
Section: Discussionmentioning
confidence: 99%
“…There were prior indications that phosphorylation promotes 26S assembly (10,18) and that dephosphorylation of Rpt6 in purified proteasomes promoted their dissociation into 20S and 19S components by disrupting the interaction between Rpt6 and α2 (10). Conversely, phosphorylation by PKA appears to promote 26S in vitro and in vivo (18).…”
mentioning
confidence: 99%
“…During the past two decades, proteasome phosphorylation has often been reported, but it remains unclear whether such modifications actually perturb rates or selectivity of protein degradation. Various subunits have been shown to be phosphorylated in vivo including four of the seven α-subunits that comprise the outer rings of the 20S particle, α7, α3, α2, and α4 (3-7), and two of the six ATPases, Rpt6 (8)(9)(10)(11) and Rpt2 (12), that comprise a ring at the base of the 19S complex. Because these rings lie adjacent to each other, their interactions are very likely to be influenced by phosphorylation and dephosphorylation.…”
mentioning
confidence: 99%